The mediating factors in the relationship between lower urinary tract symptoms and health-related quality of life. (December 2017) - Chin, Weng-Yee; Choi, Edmond; Wan, Eric; Lam, Cindy
Abstract Objectives An earlier study found that mental health partially mediates the relationship between lower urinary tract symptoms (LUTS) severity and health-related quality of life (HRQOL). In other words, LUTS adversely affects mental health, which in turn adversely affects HRQOL. A major limitation of the previous study was its cross-sectional design. The aim of this study is to evaluate whether changes in mental health mediated the association between changes in the severity of LUTS and changes in HRQOL over 24 months by using Baron and Kenny's regression procedure and Preacher and Hayes's bootstrapping method. Results We found that changes in mental health were a mediator in the relationship between the change of LUTS severity and the change of LUTS-specific HRQOL. Changes in LUTS severity lead to changes in mental health, which in turn affects the change of LUTS-specific HRQOL. It was observed however that changes in mental health did not mediate the relationship between the change of LUTS severity and the change of the physical aspects of generic HRQOL. These findings suggest that in order to optimize LUTS-specific HRQOL, both LUTS severity and mental health may need to be addressed concurrently.